Intrinsic size effect of CuTa/Cu nanolaminates with unequal modulation ratios. (15th March 2017) - Gu, C; Huang, P; Liu, M B; Xu, K W; Wang, F; Lu, T J
Abstract: In order to study the intrinsic size effect of nanolaminates with unequal modulation ratios, CuTa/Cu nanolaminates with identical Cu layer volume fraction but different Cu layer thicknesses were prepared by varying the number of Cu layers. The hardness and indentation morphology of each CuTa/Cu nanolaminate was characterized by means of nanoindentation and scanning electron microscope. Furthermore, the microstructures of CuTa/Cu nanolaminates with different interfacial configurations were examined under high resolution transmission electron microscopy. The deformation of CuTa/Cu nanolaminates was found to be dominated by the thickness ratio between CuTa and Cu layers as well as the interfacial microstructure. Graphical abstract: